2021
DOI: 10.1111/vsu.13642
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment and outcome of sterile prostatic cysts in dogs

Abstract: Objective To describe the surgical treatment and outcome of a large cohort of dogs with sterile prostatic cysts (PCs). Study Design Retrospective study. Animals Forty‐four client‐owned dogs. Methods Dogs with sterile PCs with at least 6 months of follow‐up were included. Clinical variables, type of surgery, complications, recurrences, and outcomes (telephonic interviews or rechecks) were recorded. Results Extra‐ and intraparenchymal cysts were diagnosed in 29 and 11 dogs, respectively. Four dogs had both types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Prostatic diseases are common in older, intact male, large-breed dogs, especially in German shepherds and Doberman pinchers ( 1 , 2 ). Post-mortem examinations have revealed that 75.6% of dogs dying from prostate-unrelated disorders have prostatic diseases ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prostatic diseases are common in older, intact male, large-breed dogs, especially in German shepherds and Doberman pinchers ( 1 , 2 ). Post-mortem examinations have revealed that 75.6% of dogs dying from prostate-unrelated disorders have prostatic diseases ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Post-mortem examinations have revealed that 75.6% of dogs dying from prostate-unrelated disorders have prostatic diseases ( 3 ). Prostatic cysts (PCs) account for 1.1–14% of all prostatic diseases ( 1 , 3 , 4 ), and approximately 42% of PCs become infected ( 1 ). Multiple cystic changes rather than large solitary cysts are more common ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations